The Extraction and Phytochemical Test of Toxic Extract of Xestospongia testudinaria Sponge - I Made Diraswantara; Wiwik Susanah Rita (Journal of Health Sciences and Medicine, 2018)
This research aims toextraction and phytochemical test of the toxic extract of the Xestospongia testudinaria sponge collected from Sanur beach, Bali, Indonesia. Extraction of the sponges was carried out by methanol at room temperature. Toxicity screening test was done based on Bhrine Shrimp Lethality Test (BSLT). The compounds of the toxic extract were performed by phytochemical test. Based on the results, it was found that the methanol extract of X. testudinaria sponges has toxic activity with LC50 of 31.62 ppm. The toxic extract contained alkaloid, steroid, polyphenol, and saponin compounds.